GLM-4.5-Air AutoMonitor-Bench Miss Rates in Mathematics Reasoning Tasks - Assignee Research (Assignee Research, 2026)
This report synthesises findings from 4 peer-reviewed papers addressing the following research question: How does the AutoMonitor-Bench Miss Rate (MR) of GLM-4.5-Air compare to other state-of-the-art LLMs like GPT-4 and Claude 3 on mathematics reasoning tasks. 11 claims were extracted from source literature; 0 were independently verified against retrieved documents. An automated multi-reviewer quality assessment produced a score of 4.0/10. This report is a machine-generated literature synthesis
Machine-generated literature synthesis.